2002
DOI: 10.1097/00008877-200205000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aframomum melegueta and Piper guineense on sexual behaviour of male rats

Abstract: The effects of aqueous extracts of Aframomum melegueta and Piper guineense on the sexual behaviour of male rats were studied, considering many criteria, such as penile erection, copulatory behaviour and orientation activities towards themselves (genital grooming) and female rats (ano-genital sniffing, mounting). For 8 days different groups of rats received a daily administration of distilled water (control) or a plant extract: A. melegueta at 115 mg/kg or P. guineense at 122.5 mg/kg. Both plant extracts stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 13 publications
3
49
0
Order By: Relevance
“…Kamtchouing et al [43] reported that oral administration of P. guineense fruit aqueous extract increased penile erection index in male rats compared to controls. By using orchidectomized rat models, androgens have been proven to be essential for normal penile erection [44][45][46].…”
Section: Piper Guineensementioning
confidence: 99%
See 1 more Smart Citation
“…Kamtchouing et al [43] reported that oral administration of P. guineense fruit aqueous extract increased penile erection index in male rats compared to controls. By using orchidectomized rat models, androgens have been proven to be essential for normal penile erection [44][45][46].…”
Section: Piper Guineensementioning
confidence: 99%
“…Fadogia agrestis (Rubiaceae) is commonly used to treat ED in Nigeria [43]. Yakubu et al [72] reported that mounting frequency and intromission frequency increased in a dosedependent manner, while mounting latency and intromission latency decreased with increasing dose and treatment duration in treated male rats compared to control after oral administration of F. agrestis stem aqueous extract.…”
Section: Fadogia Agrestismentioning
confidence: 99%
“…Aframomum melegueta (Guinea pepper) is a spice from the ginger family obtained from the seeds of the plant. It has been shown to increase rat sexual behavior and improve penile erection (Kamtchouing et al, 2002). The dried fruit of Piper guineense (West African Pepper) has also been shown to have the same properties as determined in the same study by Kamtchouing.…”
Section: Historical Aphrodisiacs Supported With Limited Scientific Stmentioning
confidence: 72%
“…In Africa, several plants such as M. whitei, E. capensis, aloe and pumpkin seed have been used for many years to improve sexual stimulation and improvement of sexual performance (Kamtchouing et al, 2002;Orisakwe et al, 2004). However, few experimental studies have been performed in order to define these claims of efficacy (Lampiao et al, 2008).…”
Section: Introductionmentioning
confidence: 99%